Photon Return On-Sky Test of Pulsed Sodium Laser Guide Star with D2b Repumping. (4th January 2016) - Jin, Kai; Wei, Kai; Feng, Lu; Bo, Yong; Zuo, JunWei; Li, Min; Fu, HanChu; Dai, XiaoLin; Bian, Qi; Yao, Ji; Xu, Chang; Wang, ZhiChao; et al.
Abstract: Sodium laser guide star (LGS) system has become one of the critical components in modern astronomical adaptive optics system (AOS), especially for the next-generation extremely large telescopes, such as the Thirty Meter Telescope and the European Extremely Large Telescope. Since the wavefront detection performance of AOS is directly related to the brightness of LGS, it is important for AOS to maximize its photon generation efficiency by all means. Sodium D2 b line repumping is such a technique that can greatly increase the returned photons for either sodium continuous wave (CW) laser or pulsed laser. This technique has been studied theoretically and field tested with a 20 W CW laser by European Southern Observatory team. However, field test results of a 20 W class pulsed laser with D2 b repumping have not been reported yet. In this paper, our latest field test results with theoretical comparison of D2 b repumping with a 20 W quasi-continuous wave (QCW) pulsed laser will be presented. With a linearly polarized beam, approximate 40% photon return enhancement was achieved when 10% of laser power was detuned to D2 b line, which agreed well with results from a rate equation-based Monte Carlo photon return simulation program. Both experiment and simulation results indicate that with a higher laser intensity projected at the sodium layer, the D2 b repumping will be more effective.